(untitled) (Bangladesh Journal of Plant Taxonomy, 2025)
Elephant rope (Sterculia villosa Roxb.) is a threatened plant species in Bangladesh. To conserve this threatened tree, research should be carried out on improvement of germination and early growth. Therefore, the objective of the study was to explore the effects of pre-sowing seed treatments on germination behavior and to assess the possibility of increasing the germination rate of Sterculia villosa. The seeds were subjected to nine pre-sowing treatments viz., T0: Seeds with no treatment (Control), T1: Seeds scrapping with sand paper at the distal end, Seeds immersed in T2: room temp. water for 24 hours, T3: hot water for 1 minute, T4: 10% concentrated H2SO4 for 1 minute, T5: 10% concentrated H2SO4 for 3 minutes, T6: 10% concentrated HCL for 1 minute, T7: 10% concentrated HCL for 3 minutes, T8: 200ppm GA3 for 24 hours, T9: Fungicide (Autostin 50 WDG) for 24 hours. The study conducted in the propagation house, revealed that pre-sowing treatments significantly (p<0.05) enhanced seed germination parameters of Sterculia villosa. Seed germination started within 2 days after seed sowing and continued up to 15 days. The highest germination percentage (50%) was observed in T8 and the lowest (20%) in T0, T3, and T7. The highest germination Index was found in T8 and the lowest in T0. T8 was found more effective in respect to faster germination, high germination percentage, germination index, seedling vigor index, speed, and energy of germination. In case of seedling growth parameters, the highest shoot length (62 cm) was found in T1 and the lowest (33 cm) in T3. Here, T1 was found more effective in case of shoot length, leaf number, leaf length, and leaf width. Bangladesh J. Plant Taxon. 32(1): 93-103, 2025 (June)